A fuzzy approach to the strategic development of human capital in the electric sector. (November 2020) - da Silva, Cleriston Fritsch Damasio; de Albuquerque, André Philippi Gonzaga; de Melo, Fagner José Coutinho; Calábria, Felipe Alves; de Medeiros, Denise Dumke
Highlights: The Fuzzy Set Theory in data processing to reduce respondent subjectivity. Employee training using a literature model to assess human capital development. The model used was adequate to evaluate the strategic development of human capital. The model was applied in two companies in the electric sector. The paper presents the factors that influence the paradigm of formation change. Abstract: Each day employees are becoming essential for organizations to stand out from their competitors in the globalized and disputed world. From this, companies began to invest in training and developing the skills of their employees. Therefore, this research aims to analyze human capital as one of the main factors of competitive differentiation between companies. For this, the research utilizes a tool in the treatment of data that do not fit in the common theories in which the limits between the distinct elements of a set are very clear: Fuzzy Sets Theory. In addition, this paper addresses the issue of training, applying a specific model to assess the development of human capital. The research presented the analysis of data collected in two companies in the electricity sector, one in the energy distribution sector and the other in the energy generation sector. Within the context, the model used was adequate in assessing the development of human capital, bringing a detailed approach to the factors that influence the training paradigm shift, presenting indicators to evaluate these factors, and how to evaluate them within an organization.